A method of two-tier storage management in virtualized data center - Zharikov, E.V. (Інститут програмних систем НАН України, 2019)
Internet of things applications and data analysis services require a high performance and resilient data storage systems. In the era of servers, networks and storage virtualization, there is a need to develop new models and methods of managing storages for the purpose of improving their performance and reducing the capital and operating costs of the IT infrastructure as a whole. In this paper the two-tier storage model and management method are proposed. The proposed method allows to increase the performance of read/write operations of virtual machines in cloud data centers without significant increase in the storage cost. The research results show that the use of two-tier storage management method allows to reduce the cost of storage by reducing the size and number of storage devices at the fastest level. The analysis of the simulation results shows that the two-tier storage and the proposed management method allows to reduce the waiting time for file access, that leads to an increase in the performance of the two-tier storage while simultaneously serving virtual machine and container requests. Problems in programming 2018; 4: 003-014